Total Sites Analysis (TSA) Implementation in Sahabat Oil Products, Lahad Datu, Sabah, Malaysia - Mohamed@Mohamad, Nurul’ Ain (IRC, 2016)
A common refinery plant that serves several processes within a site needs a concise energy target solution prior to the high level of complexity in terms of integrated utility system. Total Sites Analysis (TSA) is an extension of Heat Integration Analysis (HI) that will centralize the heating and cooling duty in such a way that the process integration is carried out by combining all possible streams from each process. In this report, the aim, the scope of study and the methodology is being analyzed and assessed. There are TSA tools which include Total Sites Profile (TSP), Total Sites Composite Curve (TSCC) and Site Utility Grand Composite Curve (SUGCC) that will be implied so that to maximize the heat recovery and minimize the utility cost.